2011
DOI: 10.1097/mao.0b013e3182117769
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Usefulness of Orthostatic Testing and Tilt Table Testing in the Evaluation of Autonomic-Associated Dizziness

Abstract: Evaluation for autonomic dysfunction should be part of the comprehensive evaluation of a dizzy patient, involving, at a minimum, orthostatic testing of blood pressure and heart rate. Patients with nonotologic dizziness and light-headedness with a normal neurotologic evaluation can reasonably be referred for HUT, even in the presence of normal in-office orthostatic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[2] It has already been shown that standing for 3 minutes correlates poorly with a full 30-minute tilt for both change in heart rate and blood pressure. [5;10] We aimed to carry out this analysis to a full 30 minutes of tilt and standing for change in heart rate given the recent description of “delayed POTS.”[12]…”
Section: Discussionmentioning
confidence: 99%
“…[2] It has already been shown that standing for 3 minutes correlates poorly with a full 30-minute tilt for both change in heart rate and blood pressure. [5;10] We aimed to carry out this analysis to a full 30 minutes of tilt and standing for change in heart rate given the recent description of “delayed POTS.”[12]…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic challenges usually consist of physical stimuli or actions that elicit changes in sympathetic and parasympathetic activity, often reflected as blood pressure and heart rate alterations. While certain tests are impractical inside an MRI environment (such as orthostatic changes elicited either by a tilt table or by changing posture from sitting to standing: Faraji et al, 2011 ; Saal et al, 2015 ), the majority of procedures involving a static body position with minimal electrical equipment are feasible (Adkisson and Benditt, 2015 ). The Valsalva maneuver can be performed in the supine position, with plastic tubing connected to a pressure sensor outside the scanner room and some form of signal/cue to indicate to the participant when to blow into the tube, and when sufficient pressure is reached.…”
Section: Functional Mri Methodologymentioning
confidence: 99%
“…Only two studies in the literature have compared AST and HUT as a method in the same sample of patients. 19 , 32 Although Faraji et al obtained twofold higher OH prevalance during HUT than AST, the retrospective nature of the study, the lack of methods following one after another (AST and HUT), and extending HUT to the 40th minute may lead to different outcomes. 32 Cooke et al retrospectively evaluated the cases between the age of 22 and 93 years, 19 whereas in the present study, only older adults were included and revealed two different prevalances by two different methods in the same sample of patients.…”
Section: Discussionmentioning
confidence: 99%